INDUKSI NANAS (Ananas comosus (L.) Merr) MELALUI KULTUR JARINGAN - Nadila Margareth; Ummi Hiras habisukan; Amin Nurokhman; Arif Yachya (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
The pineapple plant cultivated in Indonesia is very diverse and is a perennial plant. Public awareness of the nutritional content in pineapple can increase the production and economic value of the fruit. Therefore, large-scale pineapple production in a relatively short time is needed, and one way to achieve this is through pineapple propagation via tissue culture.  In this study, pineapple was propagated using shoot explants. Shoot culture, or shoot induction, is one method for propagating plants in vitro. Shoot culture is the most common propagation method because shoots contain a lot of meristematic tissue (which is still actively dividing), resulting in a higher percentage of success for tissue culture.  This study used a completely randomized design (CRD) with the following hormone concentrations: 0 ppm NAA + 0 ppm Kinetin, 0.25 ppm NAA + 3.0 ppm Kinetin, and 0.25 ppm NAA + 4.5 ppm Kinetin. The results showed that explant growth occurred in every concentration, with 100% of all treatments producing shoots. Nevertheless, there were variations in the number of leaves formed in each treatment and observation time, indicating the influence of hormone concentration on the vegetative development of the explant.